Rethinking the Structures of Academic Writing in the Times of Exacerbated Inequity: An Introduction - Zwagerman, Sean; Mitchell, Kim M. (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
An introduction to the special issue for Rethinking the Structures of Academic Writing in the Times of Exacerbated Inequity. This paper presents a discussion of the inspiration for this special call for papers, an analysis of the genre presentation of the typical critical examination of problems emerging from social inequities, and a summary of each of the papers contained within the special issue.